(untitled) (PerCursos, 2022)
In this paper, we provide a conjuntural analysis of the Brazilian conservative wave, based on a dialogue with the work of Milton Santos. We examine what’s revealed by the used territory in order to understand the role of communication in the conjuncture. We also examine how the organization of communication in Brazil affects the debate of projects for the future of the territory. Our focus is on the tension between innovation and previously existing dynamics in spatial arrangements. To do so, we mobilize the concepts of psychosphere-technosphere, events and socio-spatial formation.